2017
DOI: 10.1021/acs.jpcc.6b12629
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of p-Type Bi2S3

Abstract: Atomic layer deposition (ALD) of bismuth sulfide (Bi2S3) is demonstrated by the sequential exposure of bismuth­(III) bis­(2,2,6,6-tetramethylheptane-3,5-dionate) [Bi­(thd)3] and hydrogen sulfide (H2S) at 200 °C. A saturated growth rate of 0.34–0.37 Å/cycle was observed by in situ quartz crystal microbalance (QCM) and verified by ex situ X-ray reflectivity (XRR) measurements throughout the ALD temperature window. As-deposited Bi2S3 films were found to be polycrystalline in nature without any preferential orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 34 publications
(61 reference statements)
3
25
1
1
Order By: Relevance
“…x S 3-y (x= y= 0, 0.25, 0.50, 0.75 and 1) lms are given in gure 15. In the M-S plot, FTO/ Ag x Bi 2-x S 3-y (x= y= 0) thin lm shows a positive slope which con rms the 'n' type conductivity of the lm [49] whereas the rest of the lms exhibited negative slopes which con rmed the prepared lms are in 'p' type conducting nature as coinciding well with the observations made from Hall-effect analysis (table 2). The reason for the conversion of conductivity type in the lms (except x= y = 0) is attributed to the formation of acceptor defect between Ag and Bi.…”
Section: Resultssupporting
confidence: 86%
“…x S 3-y (x= y= 0, 0.25, 0.50, 0.75 and 1) lms are given in gure 15. In the M-S plot, FTO/ Ag x Bi 2-x S 3-y (x= y= 0) thin lm shows a positive slope which con rms the 'n' type conductivity of the lm [49] whereas the rest of the lms exhibited negative slopes which con rmed the prepared lms are in 'p' type conducting nature as coinciding well with the observations made from Hall-effect analysis (table 2). The reason for the conversion of conductivity type in the lms (except x= y = 0) is attributed to the formation of acceptor defect between Ag and Bi.…”
Section: Resultssupporting
confidence: 86%
“…191 Liu et al 43 first reported an ALD process for growing Bi 2 S 3 films via an R3 route. The crystalline Bi 2 O 3 films were first deposited via an ALD using Bi(thd) 3 (thd = 2,2,6,6-tetramethyl-3,5-heptanedionato) and H 2 O precursors at 300 C and were then converted to orthorhombic Bi 2 S 3 through a post-sulfurization process in sulfur vapor at 500 C. Subsequently, Mahuli et al 185 used Bi(thd) 3 and H 2 S to grow Bi 2 S 3 films directly via ALD in the range of 125 C-300 C. The GPC was constant (0.34-0.37 Å /cycle) in the range of 175 C-250 C. Otherwise, the GPC was lower at lower and higher temperatures, caused by either limited reactivity or increased desorption of precursors. The as-deposited Bi 2 S 3 films at 200 C were the polycrystalline orthorhombic phase with high purity.…”
Section: Sb 2 Tementioning
confidence: 99%
“…Table 2 summarizes the main ALD conditions as well as the eventual applications of each 2D material. 154 These processes are performed at low to mid temperature (100-250 °C), expected for GeS ALD taking place near room temperature (50-75 °C). Indeed, in this case, desorption phenomenon occurs above 150 °C.…”
Section: Fabrication Of Other Layered Chalcogenidesmentioning
confidence: 99%